PROBLEMATIKA PENGGUNAAN TEKNOLOGI BLOCKCHAIN DI SEKTOR INDUSTRI JASA KEUANGAN INDONESIA - Livia Azzura Putri; Dona Budi Kharisma (Jurnal Privat Law, 2024)
This articles aim to identify legal problems in the use of Blockchain technology in the financial services industry in Indonesia. In addition, this study also analyzes theurgency  of  forming  laws  and  regulations  on  Blockchain  technology  in  the Indonesian financial services industry sector. This type of research is normative legal research. The research approach used in this research is the statute approach. Legal materials used in this research are primary and secondary legal materials. The data collection technique used is literature study. The results showed that Blockchain technology has been utilized in several sectors of the financial services industry in Indonesia. However, the use of Blockchain technology still leaves some room for problems. From the legal aspect, some of these problems include the absence of laws and regulations governing Blockchain, risk and legal issue the using Blockchain technology for Financial Crime and not optimal monitoring of the use of Blockchain technology. This condition certainly creates serious risks related to transaction security, data breaches and monetary system stability. In this regard, the use of Blockchain technology has an urgency to be regulated in the laws and regulations in Indonesia.